Emotional Intelligence’s Role on Turnover Intention through Job Satisfaction as a Mediating Variable - Suwandana, I Gusti Made (Devotion : Journal of Research and Community Service, 2024)
Turnover intention is a condition where someone wants to leave his job or the organization he owns to get a better job. This turnover intention is a problem for businesses, but if controlled appropriately and logically, it can be a good thing. The purpose of this study was to determine the effect of emotional intelligence on turnover intention with job satisfaction as a mediating variable in workers in Denpasar coffee shop, Bali. This research uses Traditional Turnover Theory as a theoretical foundation. The sample in this study amounted to 100 people with saturated sampling techniques. Data analysis techniques use path analysis, classical assumption testing, and mediation role testing. The results showed that emotional intelligence had a negative and significant effect on turnover intention; emotional intelligence had a positive and significant effect on job satisfaction; and job satisfaction had a negative and significant effect on turnover intention; job satisfaction mediated the influence between emotional intelligence and turnover intention. This research is a consideration and input for all coffee shops in the Denpasar area, Bali to improve their internal management system.